Winter distribution of Tundra Swans Cygnus columbianus breeding in Alaska and Western Canadian Arctic - Limpert, Roland J; Sladen, William J L; Allen, Jr, Hubert A (Wildfowl, 2013)
A total of 1,499 Tundra Swans was captured on their Alaskan and Canadian breeding grounds to determine their migration routes and wintering destinations. In 14 summers of banding (1968-81) 976 (65%) swans were marked with colour neckbands, 482(32%) with colour tarsal bands, and 41 (3%) with metal bands only. Observations of the marked swans on migration or during the winter were used to determine the breeding areas used by two populations; Eastern (EP) and Western (WP). WP Tundra Swans were found to breed in Alaska from Point Hope to the Aleutian Islands. The EP breeding range overlapped with the WP in Alaska from the Yukon Delta to Point Hope. Swans breeding east of Point Hope were all associated with the EP. Only 11 individuals (<1%) of 4,194 Tundra Swans marked on the wintering grounds of EP were later encountered in the WP. No evidence of an age or sex bias was found in the likelihood of a swan switching between the two populations. Additional bandings are needed in the area of breeding range overlap to better define the relationship between the two populations.